Research on the Practice and Optimization of Macau Urban Bus Priority Policy - Junzhang Chen; Yile Chen (Asian Journal of Management Analytics, 2022)
The policy of "bus priority" solves the problem of urban residents' travel and is an important part of urban construction. This paper analyzes the research progress and implementation of "bus priority" at the current stage in China and the problems existing in the current situation of urban trans-portation in the practice of "bus priority" in Macau through literature analysis. The results show that although large cities in China have better implemented the "bus priority" policy, there are large differences among cities, the coverage is small, most small cities have less literature, and the in-vestment in research and construction is insufficient. At this stage, people pay more attention to the punctuality, convenience, benefit and convenience of public transport. The author provides some feasible reference suggestions for the future development environment, infrastructure construction, social value and economic level of "bus priority" in Macau.